(untitled) (Al-Academy, 2026)
The associative presence that characterizes the creative artistic process in its visual construction is one of the essential pillars of the visual formation process. This formation determines the entire visual structure of the television series and establishes its profound connection to the inherent aesthetic value within it. The role of the television image is not limited to being a visual form within a frame, but rather becomes an integrated structure manifested through the visual composition with its main elements and sub-components. Furthermore, visual language, as an artistic tool, is capable of producing an authentic achievement at the levels of artistic form and dramatic content, which together constitutes what is known as visual construction. From this standpoint, the television image possesses a set of visual and aesthetic components that enable it to present itself as both an art and a craft. These elements contribute to shaping its structure and supporting the process of narrating the dramatic events within the television series. The moving image here is not merely a carrier of events; rather, it is a means of capturing the imagination and transforming it into multiple meanings, whose connotations are renewed by different methods of employment and formation. Accordingly, visual construction, in its artistic and dramatic dimensions, is linked. Closely linked to the ability to realize the series’ integrated artistic structure, the artistic engagement of visual composition and pictorial language imposes its presence within the dramatic context with deliberate awareness and organized intent, its impact clearly manifesting through the technical energies and visual treatments that work to fulfill the requirements of the artistic concept. This structure, in its formative essence, works to realize the artistic vision of the dramatic concept, giving the series a distinct form, especially in light of the technological boom witnessed by the new millennium, which elevated the television image to high levels of ability to create a visual form in which aesthetic features are clearly manifested and integrated through visual technologies capable of fulfilling the expressive and functional requirements of the artistic concept.